2020
DOI: 10.1097/qai.0000000000002400
|View full text |Cite
|
Sign up to set email alerts
|

Use of Coronary Artery Calcium Scoring to Improve Cardiovascular Risk Stratification and Guide Decisions to Start Statin Therapy in People Living With HIV

Abstract: Background: Cardiovascular disease (CVD) risk assessment remains a critical step in guiding decisions to initiate primary prevention interventions in people living with HIV (PLWH). Setting: We investigated whether coronary artery calcium (CAC) scoring allowed a more accurate selection of patients who may benefit from statin therapy, compared with current risk assessment tools alone. Methods: Cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We identified 119 articles for full review on literature search, of which 43 articles were retained. 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Of the retained articles, 22 represented multiple publications from 6 different studies, * yielding 27 unique studies included in the meta‐analyses ( Table ). The aforementioned 22 articles were retained because they provided complementary data to the information reported in the leading articles.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 119 articles for full review on literature search, of which 43 articles were retained. 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Of the retained articles, 22 represented multiple publications from 6 different studies, * yielding 27 unique studies included in the meta‐analyses ( Table ). The aforementioned 22 articles were retained because they provided complementary data to the information reported in the leading articles.…”
Section: Resultsmentioning
confidence: 99%
“…Raggi et al has demonstrated that calcium scores >100 is an independent risk factor for cardiac events in HIV-positive patients (8). In addition, Paerira et al have demonstrated the utility of calcium scores to reclassify individual risk in HIV-positive populations (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated each score individually or in combination with other risk estimators. Pereira et al demonstrated that when the CAC score was combined with other scores, such as QRISK2 and FRS, they improved the risk assessment in HIV patients [27]. Likewise, others have demonstrated that using the ASCVD score can improve CAC prediction and thus enhance the type of treatment provided to CAC patients [28].…”
Section: Discussionmentioning
confidence: 99%